2006
DOI: 10.1063/1.2229197
|View full text |Cite
|
Sign up to set email alerts
|

Reactive and nonreactive scattering of N2 from Ru(0001): A six-dimensional adiabatic study

Abstract: ). Reactive and nonreactive scattering of N-2 from Ru(0001): A six-dimensional adiabatic study. Journal of Chemical Physics, 125(11), 114706. DOI: 10.1063/1.2229197 Reactive and nonreactive scattering of N 2 from Ru"0001…: A six-dimensional adiabatic study We have studied the dissociative chemisorption and scattering of N 2 on and from Ru͑0001͒, using a six-dimensional quasiclassical trajectory method. The potential energy surface, which depends on all the molecular degrees of freedom, has been built applyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 73 publications
6
54
0
Order By: Relevance
“…[29] With this as a basis the experimental data could still be consistent with a vibrational efficacy less than or equal to one. [29] However, theoretical results for N 2 dissociation on Ru(0001) indicates that the asymptotic reactivity is about the same for the different molecular vibrational states, [30] The goal of our present contribution is to show that there is actually nothing surprising about finding Θ vib (R) > 1. We will do this by providing rather straightforward considerations along the lines already suggested by Smith and coworkers, [24] leading to the conclusion that the vibrational efficacy is not limited either from below or above.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…[29] With this as a basis the experimental data could still be consistent with a vibrational efficacy less than or equal to one. [29] However, theoretical results for N 2 dissociation on Ru(0001) indicates that the asymptotic reactivity is about the same for the different molecular vibrational states, [30] The goal of our present contribution is to show that there is actually nothing surprising about finding Θ vib (R) > 1. We will do this by providing rather straightforward considerations along the lines already suggested by Smith and coworkers, [24] leading to the conclusion that the vibrational efficacy is not limited either from below or above.…”
Section: Introductionmentioning
confidence: 92%
“…The cutoff energy for the plane wave basis was set to 350 eV and to sample the Brillouin zone 18 Chadi-Cohen [39] kpoints were used. Extensive testing of all computational parameters at a number of selected configurations shows that the molecule-surface interaction energies are converged within 0.1 eV [30,31], a typical error bar for these type of DFT calculations. [40][41][42] B. Quasi-classical dynamics Classical dynamics is a very powerful tool for the kind of study we have carried out here.…”
Section: A the Dft Calculations And The Pes Representationmentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18][19][20][21][22][23][24] In some cases, non-adiabatic dynamics based on low-dimensional calculations has resulted in overestimation of the effects associated with e-h pair excitations. For example, for N 2 /Ru(0001) it was claimed, 16 based on low-dimensional non-adiabatic calculations, that the huge discrepancy between low-dimensional adiabatic calculations and experiment was mostly due to e-h pair excitations, whereas a subsequent adiabatic high-dimensional dynamics study 25,26 showed that most of the discrepancy vanishes when the six degrees of freedom of the molecule are taken into account in the dynamics. Six-dimensional (6D) adiabatic calculations have also been able to reproduce, for instance, experimental measurements of reactive and non-reactive scattering of H 2 from Pt(111) (Ref.…”
Section: Introductionmentioning
confidence: 99%